A neuroscientist's guide to transgenic mice and other genetic tools. (January 2020) - Navabpour, Shaghayegh; Kwapis, Janine L.; Jarome, Timothy J.
Highlights: Mouse knock-outs and knock-ins help identify the function of specific genes but often lack temporal and spatial control. Tet-On and Tet-Off systems allow temporal and reversible control over specific manipulations. Conditional knockouts (e.g. Cre/lox) have better spatial and temporal resolution than non-specific global knockouts. TRAP and TetTag techniques use IEG promoters to allow for tagging of active neurons during specific phases of behavior. CRISPR/Cas9 can alter endogenous gene expression through deletion, knock-in, and transcriptional activation or repression. Abstract: The past decade has produced an explosion in the number and variety of genetic tools available to neuroscientists, resulting in an unprecedented ability to precisely manipulate the genome and epigenome in behaving animals. However, no single resource exists that describes all of the tools available to neuroscientists. Here, we review the genetic, transgenic, and viral techniques that are currently available to probe the complex relationship between genes and cognition. Topics covered include types of traditional transgenic mouse models (knockout, knock-in, reporter lines), inducible systems (Cre-loxP, Tet-On, Tet-Off) and cell- and circuit-specific systems (TetTag, TRAP, DIO-DREADD). Additionally, we provide details on virus-mediated and siRNA/shRNA approaches, as well as a comprehensive discussion of the myriad manipulations that can be made using the CRISPR-Cas9 system, including single base pair editing and spatially- and temporally-regulated gene-specific transcriptional control. Collectively, this review will serve as a guide to assist neuroscientists in identifying and choosing the appropriate genetic tools available to study the complex relationship between the brain and behavior.